Unraveling the Drift: Understanding the Accelerated Movement of Earth's Magnetic North Pole toward Siberia - Goshu, Belay Sitotaw (Britain International of Exact Sciences (BIoEx) Journal, 2025)
The Earth's magnetic field has been experiencing a noticeable shift in recent decades, with the magnetic North Pole gradually drifting towards Siberia. The accelerated migration of the magnetic North Pole and its implications for comprehending the dynamics of the Earth's geomagnetic environment are examined in this study. Using historical data and linear regression models, we analyze the rate and pattern of the pole's movement, focusing on its trajectory toward Siberia. The results show a steady drift of approximately 10 kilometers per year, with predictions suggesting that by 2025, the magnetic North Pole will be located at 90.29 degrees latitude and 115.84 degrees longitude. The study also examines geomagnetic reversal events, noting significant occurrences in 1850, 1900, 1950, and 2000, and forecasts another reversal in 2025. These findings shed light on the natural variability of Earth's magnetic field and emphasize the need for continued monitoring. The study highlights the importance of understanding the magnetic field's behavior for navigation systems, satellite communication, and geophysical exploration. Furthermore, it raises questions about the long-term effects of these shifts on Earth’s magnetic environment and its interactions with solar wind. This research provides valuable insights into the ongoing changes in the Earth's magnetic field and underscores the importance of monitoring geomagnetic changes for scientific, technological, and environmental purposes.